Intercultural sсholarly discussion as an object of methodological modelling in FLT - Altun, Işıl; Khalel, A. (Farabi Journal of Social Sciences, 2020)
The article deals with the problems of methodological modeling of intercultural scientific discussion in a foreign language as an international academic measure implemented through intercultural academic interaction of representatives of various cultural,linguistic and research communities. For professional-branch communicative preparation of students of language specialties for effective participation in this scientific event in a foreign language it is necessary: a) to determine the conceptual content of the term “intercultural scientific discussion”; b) to identify the nomenclature of sequential fragmentation of intercultural communicative macro education in the micro education term on the basis of didactic-oriented content analysis of the system of activity for participants of intercultural scientific discussion in the socio-cultural academic role; c) to identify the main types of professional task assignments (in the context of international and national universities standards) created by a hierarchical system of foreign language for consistent and dynamic communicative and cognitive development of students as an equal participant of intercultural academic communication. At the same time, in the field of domestic linguistics, there is still a tendency to ignore the intercultural aspect of teaching discussions using methodological researches in Universities. This process continues in domestic science, despite the fact that such universal competencies as “communication” and “intercultural interaction” (in the formation of these competencies, the University plays a key role in language teaching), are manifested as educational results in all languages studied in the Universities. Key words: intercultural academic communication, intercultural scientific discussion, socio-cultural academic roles, intercultural communicative macro and micro educations, professional-profile and cultural-oriented problem tasks.